(untitled) (Physical Education, Health and Social Sciences, 2026)
Counselling psychology focuses on interpersonal and technical skills that are required in successful professional practice. Role-play is a teaching strategy through experiential learning that is commonly used in the counselling teaching activities in order to support the acquisition of skills but systematic measurement of skill acquisition in counselling through standardized measures is scarce. In the current paper, the author will focus on the relevance of structured role-play activities in the development of counselling competencies and will identify the effectiveness of instructor-based assessment by using the Counselling Skills and Competencies Tool (CSCT). Using theoretical backgrounds on the counselling psychology and past empirical studies, this research will help to fill gaps in the literature regarding competency-based assessment in educational contexts. The research questions and hypotheses are centered on the development of skills, validity of the assessment, and the correlation between the performance in role playing and the perceived competence and confidence of students. The results will have a potential impact on evidence-based teaching in counselling psychology education in terms of supporting systematic experiential learning and regular assessment procedures.